3xy+7x+6x+8xy=

Simple and best practice solution for 3xy+7x+6x+8xy= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3xy+7x+6x+8xy= equation:


Simplifying
3xy + 7x + 6x + 8xy = 0

Reorder the terms:
7x + 6x + 3xy + 8xy = 0

Combine like terms: 7x + 6x = 13x
13x + 3xy + 8xy = 0

Combine like terms: 3xy + 8xy = 11xy
13x + 11xy = 0

Solving
13x + 11xy = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'x'.
x(13 + 11y) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(13 + 11y)' equal to zero and attempt to solve: Simplifying 13 + 11y = 0 Solving 13 + 11y = 0 Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 11y = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 11y = 0 + -13 11y = 0 + -13 Combine like terms: 0 + -13 = -13 11y = -13 Add '-11y' to each side of the equation. 11y + -11y = -13 + -11y Combine like terms: 11y + -11y = 0 0 = -13 + -11y Simplifying 0 = -13 + -11y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

x = {0}

See similar equations:

| p=-12.5t+100 | | 0.5y+0.2y=0.3y+2 | | 13-1(2x+4)=35 | | 3.1x+2=-0.5 | | 15+-8=x | | 4(2x-3)(4x+5)=0 | | 6(a+2)-2(2a+5)=18 | | 12x^2+24x-288=0 | | (7x+16)+(9x-12)=180 | | 15x+3x=180 | | 9t+-21=3(t+-7)+6t | | 4(3x+1)+4=13x+4 | | 15x-9-4x+9= | | n^2+n=45 | | 9l-22=23+4l | | X=-8+15 | | 4m+6=17 | | 13w+39= | | y-2=.666x-27 | | 3.3x-4.2=-0.4 | | y-(-5)=-11 | | 11y-7.5-7y=2 | | C=3.50p+550 | | 48+12s= | | 8(e+6)=3(e+33) | | -34+x+36=32 | | (2x+5)=(3x-8) | | 4(2b+-6)+11=8b+-13 | | 1.5y-7=0.5y | | 5+x+x=2x+6 | | y-7=-.5x-(-6) | | 4a+10=8a+2 |

Equations solver categories